RALA-mediated delivery of FKBPL nucleic acid therapeutics. (October 2015) - Bennett, Rachel; Yakkundi, Anita; McKeen, Hayley D; McClements, Lana; McKeogh, Thomas J; McCrudden, Cian M; Arthur, Kenneth; Robson, Tracy; McCarthy, Helen O
Aims: RALA is a novel 30 mer bioinspired amphipathic peptide that is showing promise for gene delivery. Here, we used RALA to deliver the FK506-binding protein like – FKBPL gene (pFKBPL) – a novel member of the immunophilin protein family. FKBPL is a secreted protein, with overexpression shown to inhibit angiogenesis, tumor growth and stemness, through a variety of intra- and extracellular signaling mechanisms. We also elucidated proangiogenic activity and stemness after utilizing RALA to deliver siRNA (siFKBPL).Materials & methods: The RALA/pFKBPL and RALA/siFKBPL nanoparticles were characterized in terms of size, charge, stability and toxicity. Overexpression and knockdown of FKBPL was assessed in vitro and in vivo .Results: RALA delivered both pFKBPL and siFKBPL with less cytotoxicity than commercially available counterparts. In vivo, RALA/pFKBPL delivery retarded tumor growth, and prolonged survival with an associated decrease in angiogenesis, while RALA/siFKBPL had no effect on tumor growth rate or survival, but resulted in an increase in angiogenesis and stemness.Conclusion: RALA is an effective delivery system for both FKBPL DNA and RNAi and highlights an alternative therapeutic approach to harnessing FKBPL's antiangiogenic and antistemness activity.